Impact of Antiretroviral Therapy on the Risk of Herpes Zoster among Human Immunodeficiency Virus-Infected Individuals in Tanzania - Kawai, Kosuke (Am J Trop Med Hyg, 2018)
We examined the incidence of herpes zoster (HZ) before and after the initiation of antiretroviral therapy (ART), and risk factors for HZ among human immunodeficiency virus (HIV)-infected individuals in Tanzania. A cohort study was conducted among HIV-positive individuals enrolled in HIV care and treatment clinics in Dar es Salaam, Tanzania. A Cox proportional hazard model was used to examine the effect of ART on the risk of HZ after adjusting for sociodemographics and time-varying clinical and nutritional factors. Among 72,670 HIV-positive individuals, 2,312 incident cases of HZ (3.2%) occurred during the median follow-up of 15 months (interquartile range: 3–35). The incidence rate of HZ significantly declined from 48.9 (95% confidence interval [CI] = 46.7–51.0) per 1,000 person-years before ART to 3.7 (95% CI = 3.3–4.1) per 1,000 person-years after the initiation of ART (P < 0.001). The risk of HZ declined with longer duration on ART. Low CD4 cell count, older age, female sex, district of Dar es Salaam, and year of enrollment were independently associated with the risk of HZ in the multivariate analysis. Low body mass index and anemia were not associated with the risk of HZ. The risk of HZ substantially declined after ART initiation in this large cohort of HIV-infected individuals. Earlier initiation of ART could reduce the risk of HZ and other opportunistic infections among HIV-infected individuals in sub-Saharan Africa.